Therapeutic targets in diabetic peripheral neuropathy: heat shock proteins - Yin, Chengzhi; Lv, Jiao; Huang, Shujia; Lang, Chenyu; Zhao, Yunyun; Wang, Guoqiang; Kan, Junming; Wang, Xiuge (Frontiers in Endocrinology, 2025)
Diabetic peripheral neuropathy (DPN), a debilitating diabetic complication, has a complex pathological mechanism involving oxidative stress, mitochondrial dysfunction, and endoplasmic reticulum stress, and there are no effective disease-mitigating treatments. Current management is restricted to glycaemic control and symptomatic analgesia, both of which offer only modest benefit and carry appreciable adverse-effect profiles. Heat Shock Proteins (HSP) are stress-inducible chaperones that counteract protein misfolding and aggregation. Through suppression of apoptosis, cytoskeletal stabilisation and immune modulation they exert neuroprotective effects relevant to DPN onset and progression. Studies have shown that HSP90 regulates neuronal plasticity and that its inhibitors restore mitochondrial function in diabetic neurons, whereas HSP70 and HSP27 exert context-dependent positive or negative regulation. Subsequent work has evaluated covalent HSP90 inhibitors, novel HSP70 agonists, Trans-activator of transduction-Heat shock protein 27 (TAT-HSP27) mediates suppression of mitochondrial apoptosis and the utility of HSP27 as a circulating biomarker. Here we synthesise recent advances in HSPs biology and DPN pathogenesis, highlight the therapeutic potential of targeting HSPs and outline translational strategies that may expedite disease-modifying therapy.